Concepções epistemológicas que fundamentam práticas educativas do professor de berçário: contribuições de uma leitura piagetiana - Custódio, Keila Beatriz Fernandes [UNESP] (2014)
This research is linked to the line of research Childhood and Education, of the Post-Graduate Education - Master - Faculty of Science and Education - FCT / UNESP Campus of Presidente Prudente. Aims to investigate which one (s) paradigm (s) epistemological (s) have guided the pedagogical practice of nursery teachers in early childhood education, in their work with children, to understand the functions of care and education as inseparable actions, so to meet a service that actually consider as subjects of rights. Failure to understand the importance of this relationship can generate routinization of basic actions not contextualized; so, try using the Piagetian view of the action as an essential tool in child development, seeking to identify the theoretical implications of the epistemological implications diagnosed in observed practices, believing that the commitment of teachers investigated certain epistemology not known, can result in determination - not the only - in the pedagogical practice. For the research that is characterized as a case study with a qualitative approach, the following methodological tools were selected: literature / document analysis, observation and questionnaire. These resources allowed the organization of data in four categories of analysis: ¬- the teacher's epistemology: conceptions of knowledge; - Teachers' conceptions of the practice: the reveal of epistemology; - Epistemological dimension: teacher and child relationship; - The care-educate the little child's daily life: understanding manifested in the teacher's epistemology...